The Society’s Perception of Social Justice and Gender Injustice in Film Enola Holmes 2 - Putri Arviani Azzahra; Danang Dwi Harmoko (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study analyzes society’s perception of social justice and gender injustice issues in film Enola Holmes 2. Set in the Victorian era, this film presents a powerful narrative about social struggles and inequalities. This study uses a descriptive qualitative method with data collection trough an online questionnaire distributed using Google Form. The data is interpreted using Fiske and Taylor’s Social Cognition Theory, which focuses on how individuals process social information to form perceptions. The result shows that the audience has a very positive perception of the character Enola Holmes as a symbol of female empowerment. A total of 40% of respondents perceive Enola as independent, 27% as smart, and 20% as strong. This consensus reflects the strong activation of modern gender schemas in the audience. Regarding social issues. 85% of the audience agreed that the film depicts gender injustice, while 75% agreed that it depicts social justice. This study concludes that the film Enola Holmes 2 is effective in communicating its social message.